Homer, Parmenides, and the Road to Demonstration - Folit-Weinberg, Benjamin (Humanities, 2022)
Parmenides invented extended deductive argumentation and the practice of demonstration, a transformative event in the history of thought. This book uncovers the origins of this development in Homeric poetic imagery and particularly Parmenides' adaptation of the image of the hodos, the road and the journey.